Efficacy and adverse effects of doxazosin in the treatment of hypertension - Sirisinghe, Roland G. (1999)
Doxazosin, a selective alpha 1 adrenoceptor antagonist recently approved for use in Malaysia, was assessed in six patients attending an outpatient hypertensive clinic. All patients had essential hypertension and their blood pressure was not under optimum control with the current medication regimen; lack of optimum control being considered as a sitting diastolic pressure of above 95 mmHg. Patients' baseline values for blood pressure, heart rate, anthropometric parameters together with haematological,biochemical and electrocardiographic parameters were established. Following this doxazosin was added at 1 mg daily and the dose titrated every two weeks until optimum control was obtained.Patients were followed upto 12 weeks of treatment and all parameters were measured again at the end of this period.All patients responded favourably and blood pressure was controlled,sitting diastolic pressure below 90 mmHg, with doxazosin 1-4mg daily. The systolic pressure fell from a mean of 164 mmHg to 141 mmHg (14%) and diastolic pressure from a mean of 99 mmHg to 86 mmHg (13%). None of the patients had any adverse effects attributable to doxazosin. Heart rate, body weight, haematological and biochemical parameters and electocardiograms did not show any significant change with doxazosin. The above findings suggest that doxazosin is an effective and well tolerated antihypertensive drug. However the significance of the findings is uncertain because of the limited numbers of patients who could be admitted to the study during the alloted time.